If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8e + -1(-2) = 6 Multiply -1 * -2 8e + 2 = 6 Reorder the terms: 2 + 8e = 6 Solving 2 + 8e = 6 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 8e = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 8e = 6 + -2 8e = 6 + -2 Combine like terms: 6 + -2 = 4 8e = 4 Divide each side by '8'. e = 0.5 Simplifying e = 0.5
| 4/9x^2=3 | | y-1/3=1/6 | | 9+5r+5r+2r= | | 30=1x-80 | | -1.4-2.7= | | 9(2x+3y)= | | 174=14.3*c*27 | | 4x-8=3y-15 | | 8h+20=69 | | 1-6(4-7x)=-23-3x | | 3(2x-5)-4x=5-4(7-x) | | 30=36a+6b+5 | | x/2-1=2x-7 | | 2(x-3)+21=-03 | | 7(x-8)-8(y+4)=80 | | -144/9 | | 30=36a+6b+c | | 27=4x+7(x-4) | | 2+-4+-5n-7+3n= | | 7x-9x+4=x-8+12 | | 2x-5(2x-10)=18 | | 8(8p+4)-8p=-27-3p | | 4g+8g+2g+9g+3g= | | 3x-5y=33-5x | | -16x-3y=12 | | 27w=-3w | | 456c=4 | | -15+5a=6a | | 10+x=5(x)+40 | | W-13.2=10.4 | | f(-6x)=6x^2-4 | | (3n+5)(n-2)-3n(n+1)=6 |